2007
DOI: 10.1016/j.jvs.2007.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Infected abdominal aortic aneurysm caused by Brucella abortus: A case report

Abstract: This case report describes an infected aneurysm caused by Brucella abortus. To the best of our knowledge, this case represents the first reported occurrence of an infected abdominal aortic aneurysm caused by this pathogen. The clinical findings included mild fever, fatigue, cold sweats, and abdominal pain. The diagnosis was reached by computed tomography scanning. The patient was treated by urgent surgery, which consisted of resection of the aneurysmal sac, prosthetic graft replacement, and omental wrapping. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…2532, 3545,47,49,50,52,53,55,56,57,58 Sulfa drugs include co-trimoxazole, terfonyl, and sulfanilamide.…”
Section: Figurementioning
confidence: 99%
“…2532, 3545,47,49,50,52,53,55,56,57,58 Sulfa drugs include co-trimoxazole, terfonyl, and sulfanilamide.…”
Section: Figurementioning
confidence: 99%
“…It is a zoonotic intracellular Gram-negative coccobacillus which causes multisystemic Malta fever, undulant fever, respiratory infections, and septicemia, especially in immunocompromised patients. It is a very rare cause for primary mycotic aortic aneurysm, 3 5 6 although there are a few case reports of primary endocarditis, ensuing septicemia, and associated focal aneurysms 4 7 of the aorta or other arteries. The mode of spread is usually from infected cattle directly, or more commonly via milk and other body fluids.…”
Section: Discussionmentioning
confidence: 99%
“…However, infection of the cardiovascular system by Brucella is uncommon, and it is even rarer that Brucella infection directly causes aortic aneurysm, which is usually secondary to endocarditis in clinic. In 2007, Park et al [ 9 ] reported the world's first Brucella -infected abdominal aortic aneurysm in South Korea.…”
Section: Discussionmentioning
confidence: 99%